The impact of entrepreneurial education on the propensity of business students to support new ventures: A moderated mediation model - Khuram, Shahzad; Ahmed, Hina; Ali, Shahzad (Frontiers in Psychology, 2022)
This research aims to investigate the role of financial self-efficacy in mediating the relationship between entrepreneurial education and venture capital intention, as well as the moderating influence of government support on the relationship between financial self-efficacy and venture capital intention. The target population consists of Lahore students from public and private universities who have already studied entrepreneurship. Based on the 250 responses to the online survey the findings show the mediating role of financial self-efficacy between entrepreneurial education and intention toward venture capital. Moreover, it also indicates the moderated effect of government support on the relationship between financial self-efficacy and intention toward venture capital. This study will not only help the curriculum committees in business schools to design entrepreneurial education outlines that enable the students to explore the different financing modes by including financial knowledge to cope with financial challenges but also to the government officials in devising financing plans accompanied by their expertise in the development of a business.